Getting started in research: systematic reviews and meta-analyses. (February 2015) - Kisely, Stephen; Chang, Alice; Crowe, Jim; Galletly, Cherrie; Jenkins, Peter; Loi, Samantha; Looi, Jeffrey C; Macfarlane, Matthew D; McVie, Ness; Parker, Stephen; Power, Brian; Siskind, Dan; et al.
Objectives: Systematic reviews are one of the major building blocks of evidence-based medicine. This overview is an introduction to conducting systematic reviews and meta-analyses. Conclusions: Systematic reviews and meta-analyses of randomised controlled trials (RCTs) represent the most robust form of design in the hierarchy of research evidence. In addition, primary data do not have to be collected by the researcher him/herself, and there is no need for approval from an ethics committee. Systematic reviews and meta-analyses are not as daunting as they may appear to be, provided the scope is sufficiently narrow and an appropriate supervisor available.